Mobilization of hematopoietic progenitor stem cells in allogeneic setting with lenograstim by subcutaneous injection, in daily or twice‐daily dosing: a single‐center prospective study with historical control. Issue 8 (9th April 2015) - Martino, Massimo; Moscato, Tiziana; Barillà, Santina; Dattola, Antonia; Pontari, Antonella; Fedele, Roberta; Furlò, Giuseppe; Marzia Stilo, Carmen; Alberto Gallo, Giuseppe; Tripepi, Giovanni
<x xml:space="preserve">Abstract</x> BACKGROUND Although the mobilization of hematopoietic progenitor stem cells from healthy donors (HDs) using granulocyte–colony‐stimulating factor is widely used, the ideal method for the administration of the cytokine has not yet been determined. STUDY DESIGN AND METHODS Seventy‐five consecutive HDs received lenograstim (LENO) as mobilization agent. LENO was given subcutaneously at a dose of 10 µg/kg in a once‐daily dose (ODD) every 24 hours. Results were compared with a historical control group of 181 HDs treated with 5 µg/kg LENO twice‐daily dose (TDD) with a time interval of 12 hours. RESULTS CD34+ cell concentrations evaluated on Day 4 and on Day 5 were 45 × 106 (range, 6 × 106‐217 × 106)/L and 75 × 106 (range, 7 × 106‐279 × 106)/L with ODD versus 36 × 106 (range, 3 × 106‐200 × 106)/L and 55 × 106 (range, 3 × 106‐738 × 106)/L with TDD (p = 0.067 and p = 0.001). The collected CD34+ cell counts in first apheresis procedure were 5.6 × 106 ± 2.9 × 106 and 5.7 × 106 ± 3 × 106/kg donor and recipient body weight in the ODD versus 5.4 × 106 ± 3.8 × 106 and 5.3 × 106 ± 3.5 × 106/kg in the TDD cohort, respectively (p = 0.08 and p = 0.02). Five HDs (6.7%) mobilized CD34+ cells of fewer than 2 × 106/kg recipient body weight in the ODD group compared with seven HDs (3.9%) in the TDD group (p = 0.3). CONCLUSIONS Once‐daily administration of LENO is at least as effective as twice‐daily administration for the mobilization of CD34+ cells in HDs.